Teaching Evolution as the Unifying Theory of Biology via a University Course: Re-Count of a Praxis - Athanasiou, Kyriacos (Interdisciplinary Journal of Environmental and Science Education, 2022)
ABSTRACT: The aim of the presentation is to discuss the findings of a series of research projects that we have been carried out with various groups of students in the University of Athens and concern the teaching of biology by means of evolution through natural selection (THES). In the article it is discussed the conclusions after teaching a biology course based on evolution as the unifying theory, while at the same time more general issues are raised: Is it, for example, a realistic goal to teach biology by means of this kind of teaching? Secondly, what is the usefulness of such a perspective. Which was studied by quantitative and qualitative studies on the conceptual ecology (CE) of the evolution of Greek students. The latter showed the value of this kind of approach in the acceptance and understanding of the THES, as part of students’ CI. Thirdly, ccomparative studies with beginners and advanced students in terms of evolution education showed, that, merely teaching evolution within a course, even if the latter is based on the THES, it is not enough to make someone in-depth connoisseur. It seems that to be acquainted with it to more depth the learners need to go through two stages: in the first, they may move from the stage of owing Aristotelian views of the issue, i.e., from typology, to the early “Darwinian” ones. And they need to go through a second one, where via, in-depth educational training, they might move to the next, namely, the population view of thinking.